Evaluación de la viabilidad de la biodigestión como sistema de tratamiento de los residuos de la granja porcina "Galo Porcino" Cantón Echeandia, Provincia de Bolívar, año 2016. - Sánchez Hinojosa, Yomely Thaily (2017)
The present research consisted in the construction of a pilot-scale biodigestor to evaluate the viability of biodigestion from porcine excreta in the "Galo Porcino" farm located in the Echeandia canton of Bolívar province. The farm has a total of 500 pigs in the Fattening stage specifically, divided into 5 cubicles, having 100 in each, generating a total of 1,160 kg / day of excreta, the animal generated dejections, are arranged through pipes to open oxidation pools located inside The same farm, taking into account this problem was made the construction of a biodigestor and for that was used a metal tank to which was adapted two stopcocks one placed at the top for the exit of the biogas and another in the part Inferior for the exit of the biol, also a gas thermometer, a crank for the constant movement of the material that is inside and ta The tank was also marked with an adhesive indicating that it is a flammable gas, the collection was carried out on January 10 by entering into the biodigester 160 L of substrate leaving 25% free for the production of biogas, temperature data were taken From the second day of operation in three different schedules (7am; 12pm; 5pm) for 75 days, the temperatures were 25 ° C and 8 days at 42 ° C, and in the last 24 days remaining constant, starting on day 40, a physico-chemical analysis was performed in the water and soil laboratory of The UTEQ, biol samples were taken and pH analyzes were performed which remained in the neutrality range (6.49), Total Solids and Total Volatile Solids once a week for a month. It is proposed the design of a biodigestor on a real scale, which treats the totally generated dejections, for which mathematical calculations are proposed, to know the daily generation of excreta per day, the volume of substrate to enter the biodigester, and the volume Of daily load, the proposed biodigestor treating the total excreta will be a Chinese type will have a dimension of 4m wide; 4m long and 3m high must be constructed of concrete material, with a semi-continuous flow, and with substrate load of 10 days, will be placed underground and its resistant characteristics will have a minimum useful life of 15 years. The construction of the biodigestor will cost $ 5618.15 including all facilities and labor, the time allocated for construction will be 2 months. The owner of the farm is recommended to construct the biodigester as a viable alternative for the proper management of organic waste and the protection of the environment, avoiding the excessive accumulation of manure.